Antimicrobial Resistant and Biofilm forming Coliforms in Drinking Water Systems of Mumbai's Harbour Line Railway Stations - Kamdar, D.; Shah, M.; Patil, S. (Journal of Scientific Research, 2025)
This study aimed to assess the microbiological quality of drinking water stored at railway station tanks in Mumbai and evaluate the prevalence of antibiotic-resistant bacteria. A total of 88 water samples were collected and analysed for presence of coliforms using standard methods. The positive samples were further tested on selective media for bacterial identification. The antibiotic resistance profiles of the isolates were assessed using a panel of 15 broad spectrum antibiotics. The presence of plasmids and biofilm forming ability of the isolates was also evaluated. The analysis revealed that all samples were contaminated with coliform and non-coliform bacteria. Among the isolates, Pseudomonas (28 %), Enterobacter (27 %), Escherichia (8 %), and Klebsiella (7 %) were the most prevalent genera. Alarmingly, all isolates produced biofilms and 82 % exhibited resistance to multiple antibiotics with 12 % harboring plasmids. These findings highlight the critical need for more stringent monitoring and management of drinking water systems to prevent the spread of AMR through water systems.